If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -105 = p Reorder the terms: -105 + 5p = p Solving -105 + 5p = p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -105 + 5p + -1p = p + -1p Combine like terms: 5p + -1p = 4p -105 + 4p = p + -1p Combine like terms: p + -1p = 0 -105 + 4p = 0 Add '105' to each side of the equation. -105 + 105 + 4p = 0 + 105 Combine like terms: -105 + 105 = 0 0 + 4p = 0 + 105 4p = 0 + 105 Combine like terms: 0 + 105 = 105 4p = 105 Divide each side by '4'. p = 26.25 Simplifying p = 26.25
| -5(r+9)=-66 | | 9w+3=3(3w+1) | | 2(n/6+22)=60 | | 3.4/0.2= | | 8(x+7)+11=10x-2(x-6) | | 12m^2+40m-32=0 | | 3x^2+5=-80 | | 3x+5+8x-4= | | 7x(h-10)= | | 4+(-20)+20= | | x+22x=90 | | 4(9c+7)= | | 29=-3x-16 | | (-1.75)(-4)= | | 6(y+x)= | | 10x+9=30+10x-21 | | 2a-5/7=3 | | 1/5*7/3 | | -2x-33=-6x-9-8x | | 2(7c-1)-8=12c+2 | | 35/x-60=400 | | 1=-3-1/3x | | 5/1/25/19= | | -1-1/2x=3 | | 10(-6a-2)=5(2-9a) | | 3x-7y=-34 | | 14-z= | | 2(7-5h)+8= | | 7-9/x=9 | | -8x-35=-x | | 1+5x=12.6 | | 7/3/-5 |